Detection of carbapenemases in Enterobacteriaceae: a challenge for diagnostic microbiological laboratories. (14th June 2014) - Hrabák, J.; Chudáčková, E.; Papagiannitsis, C. C.
Abstract Carbapenemase‐producing bacteria have now spread all over the world. Infections caused by those bacteria are difficult to treat. Therefore, there is an urgent need for accurate and fast detection of carbapenemases in diagnostic laboratories. In this review, we summarize screening methods for suspected isolates, direct assays for confirmation of carbapenemase activity (e.g. the Carba NP test and matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry carbapenem hydrolysis assay), inhibitor‐based methods for carbapenemase classification, and molecular‐genetic techniques for precise identification of carbapenemase genes. We also propose a workflow for carbapenemase identification in diagnostic laboratories.